Cultural aspects in the management of bovine diseases in an Amazonian district of Peru - Cubillas, Elizabeth (2021)
The aim of this study was to identify cultural aspects in the management of diseases that affect the health of cattle among cattle farmers in the Aguaytía district, Ucayali, Peru. Interviews were conducted with farmers and sellers of veterinary products in the area following a script of previously validated questions. Additionally, the National Agrarian Health Service (SENASA) was asked for information about the diseases reported in the region during the last two years. The description of the management of the health aspects was obtained from the assessment made by the interviewees. Rabies, anthrax and parasitosis were the diseases recognized as the most frequent in the study area. Farmers recognize the main clinical signs compatible with the main diseases, so they do not resort to the services of independent veterinarians or SENASA for confirmation. This has promoted the medication and sale of pharmacological products without a veterinary prescription. SENASA was required mainly to carry out the campaigns of the disease programmes under official surveillance, such as rabies and anthrax. The study offers preliminary information about the cultural aspects of bovine health management in the region that can be used as a basis for proposing future studies and development programs for this productive activity in the region.